Theoretical Kinetic Study of Thermal Decomposition of 5-Methyl-2-ethylfuran - Wei He; Cheng Wang; Qichuan Zhang; Kaixuan Chen; Linghao Shen; Yan Li; Kang Shen (Molecules)
With the advancement of new synthetic techniques, 5-Methyl-2-ethylfuran (5-MEF) has emerged as a promising renewable biofuel. In this study, the potential energy surfaces for the unimolecular dissociation reaction, H-addition reaction, and H-abstraction reaction of 5-MEF were mapped at the CBS-QB3 level. The temperature- and pressure-dependent rate constants for these reactions on the potential energy surfaces were determined by solving the master equation, using both transition state theory and Rice–Ramsperger–Kassel–Marcus theory. The results showed that the dissociation reaction of the C(6) site on the branched chain of 5-MEF has the largest rate constant and is the main decomposition pathway, while the dissociation reaction of the H atom on the furan ring has a lower rate constant and is not the main reaction pathway. In addition, the dissociation of H atoms on the branched chain and intramolecular H-transfer reactions also have high-rate constants and play an important role in the decomposition of 5-MEF. H-addition reactions mainly occur at the C(2) and C(5) sites, and the generation of the corresponding products through β-breakage becomes the main reaction pathway. With the increase in temperature, the H-addition reaction at the C(2) site gradually changes to a substitution reaction, dominating the formation of C2H5 and 2-methylfuran.